EFFECT OF CYSTEIN HYDROCHLORIDE AND VITAMIN E SUPPLEMENTATION ON QUALITY OF CRYOPRESERVED HARIANA BULL SEMEN - SINGH PAL, AJENDAR; SINGH, VIJAY; PATEL, AKHIL (The Indian Journal of Animal Reproduction, 2022)
The present study was aimed to evaluate the beneficial effects of supplementation of cystein hydrochloride and Vitamin E on seminal attributes during different stages of semen cryopreservation in Hariana bull. Thirty two ejaculates from four Hariana bulls were collected after initial examination the qualified ejaculates were divided into three aliquots; one aliquot was extended with glycerolated egg yolk tris citrate (GEYT) extender (Control), second aliquot was extended with GEYT supplemented with Cystein hydrochloride @ 5.0 mM (T1) and the third aliquot was extended with GEYT supplemented with VitaminE @ 2.5 mM (T2). All semen samples were equilibrated and cryopreserved. The effect of cystein hydrochloride and vitamin E was determined by assessment of sperm viability, progressive motility, hypoosmotic response, and acrosomal integrity at three stages i.e. after dilution, pre-freeze and post –thaw. It was observed thatsupplementation of cysteine hydrochloride (5mM) and vitamin-E (2.5 mM) caused significant (P<0.05) increase in all sperm attributes at post thaw semen.